Upper endoscopy versus endosonography in differential diagnosis of gastrointestinal bulging - Ardengh,José Celso (2011)
CONTEXT: The identification of a bulging covered by normal epithelium is a common finding during an upper gastrointestinal endoscopy. OBJECTIVE: To compare the endoscopic and endosonography findings in the differential diagnosis of the gastrointestinal bulging (subepithelial tumor or extrinsic compression). METHOD: Patients referred by endosonography with bulging of upper gastrointestinal tract were studied retrospectively. The size, location, consistency and presumptive diagnosis were recorded at time of endoscopy and endosonography. Endosonography-guided fine-needle aspiration was proposed in case of uncertain diagnose to increase diagnostic sensitivity. RESULTS: One hundred seventy-six patients (93 women) and mean age 62.5 years (10-87). One hundred fifty-three had subepithelial tumor and 23 had extrinsic compression as a final diagnosis. Endosonography had sensitivity, specificity and accuracy higher than those found by endoscopy for both diagnosis subepithelial tumor and extrinsic compression. Endoscopy and endosonography showed poor concordance (K = 0.13) for subepithelial tumor diagnosis and unsuitable agreement for diagnosis in extrinsic compression (K = 0.01). The endosonography-guided fine-needle aspiration had sensitivity, specificity, positive predictive value, negative predictive value and accuracy of 75%, 72.4%, 80.5%, 65.6% and 74%, respectively. CONCLUSION: Endoscopy has high sensitivity and low specificity for subepithelial tumor and both are low for the extrinsic compression. Endoscopy is a good tool for diagnosis of the subepithelial tumors, but not to determine the cause of an extrinsic compression. The endosonography identifies the layer from which subepithelial tumor comes, obtain histological samples, and increasing the diagnostic accuracy.